Autonomous Maintenance as a Pillar of total Productive Maintenance (TPM) in a Ceramic Plant - Gonzalo Moreno, Edwin Espinel Blanco, Eder Norberto Florez Solano (International Journal of Advanced Science and Technology, 2020)
This paper presents the implementation of the autonomous maintenance pillar based on the principles of total productive maintenance (TPM) in a ceramic tiles plant. In order to reduce the contamination of the process and achieve the objective of sustainable production, the proposed methodology was applied. This methodology was structured in three stages that make up the 7 steps described in the literature to achieve the overall application of autonomous maintenance: standardizing the basic conditions (three steps), maintaining the basic conditions (two steps), and systematically improving the conditions of the machine (two steps). The strategy applied reduced large amounts of waste and contamination by dirt, noise, heat, and odor generated in the ceramic tiles plant, which resulted in lower energy consumption as well as lower maintenance and production costs. Through the use of performance indicators, effective compliance with the cleaning, inspection, lubrication, and adjustment standards was verified, as well as autonomous maintenance activities carried out by the equipment operators, which allowed the reduction of waste and contamination of the process.